2019
DOI: 10.1016/j.neuron.2019.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of GABAergic Interneurons in the Barrel Cortex during Active Tactile Behavior

Abstract: Highlights d Spikes were recorded from cortical E, FS, SST, and VIP neurons during active touch d Whisking and touch activate FS neurons in the VPM thalamorecipient layers d Touch activates SST neurons with a delay d VIP neurons are excited during whisking

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
215
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(259 citation statements)
references
References 120 publications
(197 reference statements)
36
215
0
Order By: Relevance
“…Additionally, in L4, only 34% of the VIP-IN axonal boutons are located on GABA+ dendrites, suggesting weak inhibitory-inhibitory interactions in this layer (Zhou et al, 2017). Muñoz et al (2017) (Fu et al, 2015), and whisker-based object localization in the go/no-go task increases the spike rates of VIP-INs in the barrel cortex (Yu et al, 2019). On the other hand, the selectivity of VIP-INs in the visual go/no-go discrimination task did not change in the course of associative learning (Khan et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, in L4, only 34% of the VIP-IN axonal boutons are located on GABA+ dendrites, suggesting weak inhibitory-inhibitory interactions in this layer (Zhou et al, 2017). Muñoz et al (2017) (Fu et al, 2015), and whisker-based object localization in the go/no-go task increases the spike rates of VIP-INs in the barrel cortex (Yu et al, 2019). On the other hand, the selectivity of VIP-INs in the visual go/no-go discrimination task did not change in the course of associative learning (Khan et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Activation of SOM-INs by acetylcholine may contribute to inhibition of PV interneurons and consequently to stronger disinhibition of principal cells. Moreover, touch-induced activation of SOM-INs, including L4, is time delayed, probably reflecting intracortical excitatory input rather than thalamic input (Yu et al, 2019); thus, L4 SOM-INs may increase their spike rates as a result of increased activity of excitatory cells during conditioning, further potentiating L4 disinhibition. SOM-PV disinhibition in the thalamocortical input layer during CS+UCS pairing may allow for wider spreading of the signal from the active vibrissae in the barrel cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The increased amplitude of evoked inhibition in the high behavioral state was also an interesting finding. Fast spiking parvalbumin expressing interneurons receive strong direct sensory input from the thalamus and are responsible for feedforward inhibition (Sermet et al, 2019;Yu et al, 2019). The increased inhibition in high state could be attributed to enhanced activation of these fast spiking interneurons.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these differences, both primary motor cortex-projecting and secondary somatosensory cortex-projecting S1 neurons could discriminate between Go and NoGo trials. Neural encoding of trial type during whisker-based object localization has also been shown to be both cell-type (Yu et al, 2019) and layer-specific, with a greater proportion of discriminating neurons located within layer 4 and 5 of the barrel cortex (O'Connor et al, 2010b). Taken Guo et al (2014b) and Chen et al (2017).…”
Section: Primary Sensory Corticesmentioning
confidence: 99%